2020
DOI: 10.1016/j.erss.2020.101555
|View full text |Cite
|
Sign up to set email alerts
|

Of impacts, agents, and functions: An interdisciplinary meta-review of smart home energy management systems research

Abstract: Smart home energy management technologies (SHEMS) have long been viewed as a promising opportunity to manage the way households use energy. Research on this topic has emerged across a variety of disciplines, focusing on different pieces of the SHEMS puzzle without offering a holistic vision of how these technologies and their users will influence home energy use moving forward. This paper presents the results of a systematic, interdisciplinary meta-review of SHEMS literature, assessing the extent to which it d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…While these cybersecurity concerns may influence individual willingness to connect energy data to a broader network, they hardly restrict the willingness to participate in smart energy systems [ 196 ]. Rather, comparative studies have shown that the smart home applications rely on techno-centric approaches, and the design and construction of the tools is not user-friendly, with a noticeable absence of holistic approaches or applied principles of human–computer interaction (HCI) as found in participatory and collaborative, open-data-based design approaches [ 197 ]. In addition, gender considerations matter in smart energy home solutions, as gender disparities are still the predominant realities of domestic labor [ 198 ].…”
Section: Community Energy and The Hope For Smart Communities Of The Futurementioning
confidence: 99%
See 1 more Smart Citation
“…While these cybersecurity concerns may influence individual willingness to connect energy data to a broader network, they hardly restrict the willingness to participate in smart energy systems [ 196 ]. Rather, comparative studies have shown that the smart home applications rely on techno-centric approaches, and the design and construction of the tools is not user-friendly, with a noticeable absence of holistic approaches or applied principles of human–computer interaction (HCI) as found in participatory and collaborative, open-data-based design approaches [ 197 ]. In addition, gender considerations matter in smart energy home solutions, as gender disparities are still the predominant realities of domestic labor [ 198 ].…”
Section: Community Energy and The Hope For Smart Communities Of The Futurementioning
confidence: 99%
“…We see in this new challenges emerging for post-pandemic energy social research [ [250] , [197] ]. Ways of re-imagining surveillance power [ 251 ] and gender aspects [ [252] , [253] ] have begun to be explored.…”
Section: Conclusion: In Search Of the Rare Chameleonmentioning
confidence: 99%
“…The devices use methods that estimate the values. A comparison of stochastic models was proposed by [101], while the interdisciplinary impact on efficiency in energy management was discussed by [102]. Home healthcare models also were covered in reviews of valuable reviews.…”
Section: F Review Reportsmentioning
confidence: 99%
“…The review presented in [203] is discussing energy management propositions over the literature. In [102] was presented research on the impacts of smart home energy management on the development in other disciplines. The studies cover also technological advances.…”
Section: Optimal Energy Management and Sustainabilitymentioning
confidence: 99%
“…The operation and coordination of these components entails technical difficulties, especially for SHT that depend on manual intervention from end users. This has led to a literature bias towards SHT solutions that require minimal consumer intervention [7].…”
Section: Introductionmentioning
confidence: 99%